1945
DOI: 10.1021/ja01217a505
|View full text |Cite
|
Sign up to set email alerts
|

REMOVAL OF GAS NUCLEI FROM LIQUIDS AND SURFACES1

Abstract: from 10-20 cc. of absolute ethanol gave 1.6 g. melting 91-92°; 70% of the theoretical yield. No depression was observed in a mixed m. p. with the product obtained before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1955
1955
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…However, higher pressures are required in order to obtain homogeneous nucleation. This fact is also supported by Harvey et al (1945), who reported that water compressed to about 100 MN/m2 and brought back to atmospheric pressure exhibited a very peculiar behavior: it could be heated above 473 K without eruption of vapor. Moreover, it was possible to transmit acoustic waves at high frequency without cavitation or formation of bubbles.…”
Section: Operating Conditionssupporting
confidence: 64%
“…However, higher pressures are required in order to obtain homogeneous nucleation. This fact is also supported by Harvey et al (1945), who reported that water compressed to about 100 MN/m2 and brought back to atmospheric pressure exhibited a very peculiar behavior: it could be heated above 473 K without eruption of vapor. Moreover, it was possible to transmit acoustic waves at high frequency without cavitation or formation of bubbles.…”
Section: Operating Conditionssupporting
confidence: 64%
“…Then, valve 2 was closed and the conditioning vessel was isolated from the atmosphere by turning the three-way tap 10. Simultaneously, valve 3 was opened and the residual pressure in the bomb pushed the suspension from the vessel into the Ñotation column (14). The rest of the procedure was the same as that described for single bubbleÈparticle capture experiments without degassing or gassing,22 with the exception that the added clean water was Ñushed with the gas under consideration or degassed accordingly.…”
Section: Experiments In Degassed or Gassed Systemsmentioning
confidence: 99%
“…14 Indeed, some reports of the nucleation of micrometric-size bubbles on hydrophobic surfaces were published long before. 15 However, no explanation for the very existence of long-lasting nanobubbles that considers the large Laplace pressure inside them has been advanced. Some researchers have even suggested that the observed nanobubbles in scanning probe experiments are a consequence of confinement effects or tipÀsubstrate interaction.…”
mentioning
confidence: 99%